Corneal confocal microscopy in chronic inflammatory demyelinating polyneuropathy. Issue 2 (28th December 2015) - Stettner, Mark; Hinrichs, Lena; Guthoff, Rainer; Bairov, Silja; Petropoulos, Ioannis N.; Warnke, Clemens; Hartung, Hans‐Peter; Malik, Rayaz A.; Kieseier, Bernd C.
Abstract: Objective: There is an unmet need for better diagnostic tools to further delineate clinical subsets of heterogeneous chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and multifocal motor neuropathy (MMN) to facilitate treatment decisions. Corneal confocal microscopy (CCM) is a noninvasive and reproducible nerve imaging technique. This study evaluates the potential of CCM as a diagnostic surrogate in CIDP and MMN. Methods: In a cross‐sectional prospective approach, 182 patients and healthy controls were studied using CCM to quantify corneal nerve damage and immune cell infiltration. Results: Patients with CIDP and MMN had a reduction in corneal nerve fiber (CNF) measures and an increase in corneal immune cell infiltrates. In CIDP, CNF parameters decreased with increasing duration of disease. The number of dendritic cells in proximity to CNFs was increased in patients with early disease and correlated with the degree of motor affection. A further reduction in CNF parameters and an increase in nondendritic cells were observed in patients with painful neuropathy. In CIDP patients with antineuronal antibodies the number of nondendritic cells was increased. Interpretation: Our findings suggest that CNF loss may reflect severity of neuropathy and quantification of distinct cells around the CNF plexus may help in stratifying CIDP subtypes, clinical course, and disease activity. However, further longitudinal studies are required before CCM can be considered as a valid surrogate endpoint for patients with CIDP and MMN.